Pengaruh Program Literasi Dasar terhadap Minat Baca Siswa Sekolah Dasar: The Influence of the Basic Literacy Program on Elementary School Students’ Reading Interest - Umiaiman Elwahan; Supriadi Supriadi; Rahma Ashari Hamzah (Madrasah Tsanawiyah DDI Cilellang, 2023)
Elementary school students’ interest in reading is still low, making it difficult to compete in the era of Industrial Revolution 4.0. This research aims to analyze: (1) the implementation of the basic literacy program; (2) the description of students’ reading interests; and (3) the influence of the basic literacy program on students’ reading interests. This research uses a quantitative approach with an ‘ex post facto’ design. The population of this study was 25 elementary school students. Sampling was carried out using a total sampling technique, so 25 samples were determined. Data collection techniques use observation, questionnaires, and documentation, which are then analyzed using descriptive and inferential statistical techniques. The research results show that the basic literacy program influences students’ reading interests. Apart from that, these two variables also have a significant linear relationship. This research has implications for the importance of getting students accustomed to reading since childhood. Of course, this habituation is not only based on binding schools' programs or policies but is accompanied by creative and innovative methods so that it can attract students’ interest.